2018
DOI: 10.1530/joe-18-0005
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian hormone overexpression restricts preantral ovarian follicle survival

Abstract: Anti-Müllerian hormone (AMH) is an ovarian regulator that affects folliculogenesis. AMH inhibits the developmental activation of the dormant primordial follicles and the oocyte within. In more mature follicles, AMH reduces granulosa cell sensitivity to follicle-stimulating hormone (FSH). We examined the effects of AMH overexpression on the stages of ovarian folliculogenesis, and the development of embryos, with a transgenic mouse that overexpresses human AMH in central nervous system neurons under the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
0
14
0
1
Order By: Relevance
“…This suggests that follicles underwent a sufficient amount of AMH action. Another AMH action is prevention of the transition from primordial to primary stages [22, 23]. In our experiments, growth was observed downstream of secondary follicles, therefore we were unable to determine the effect of pioglitazone on primordial follicles.…”
Section: Discussionmentioning
confidence: 86%
“…This suggests that follicles underwent a sufficient amount of AMH action. Another AMH action is prevention of the transition from primordial to primary stages [22, 23]. In our experiments, growth was observed downstream of secondary follicles, therefore we were unable to determine the effect of pioglitazone on primordial follicles.…”
Section: Discussionmentioning
confidence: 86%
“…This depletion occurred acutely during the first 30 days of initial release, and no further loss was observed on days 30 to 50, during which time antral follicle counts and endogenous mMIS levels returned to normal. Alternatively, some of the ovarian reserve loss may be the direct consequence of prolonged and elevated exposure to superphysiological levels of MIS, which in transgenic models appears to be harmful to both follicles and egg quality [35]. In our model, however, egg viability appears to be unaffected, suggesting the adverse effects of MIS exposure on follicle health observed in these studies may be the sequela of fetal or neonatal exposure during follicular assembly [3537].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, some of the ovarian reserve loss may be the direct consequence of prolonged and elevated exposure to superphysiological levels of MIS, which in transgenic models appears to be harmful to both follicles and egg quality [35]. In our model, however, egg viability appears to be unaffected, suggesting the adverse effects of MIS exposure on follicle health observed in these studies may be the sequela of fetal or neonatal exposure during follicular assembly [3537]. Further studies examining the consequence of MIS pretreatment on early embryonic development of the zygote will be needed to confirm the lack of adverse effects on egg quality using a nonimmune compromised mouse model more suited for in vitro embryo maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have been performed in adult mice, which may provide insight into the contribution of elevated bioactive AMH in the PCOS pathophysiology (summarized in Figure 1). Kano et al and Pankhurst et al [32,33] both showed that treatment with supraphysiological levels of AMH resulted in a phenotype that resembles ovarian insufficiency rather than PCOS, because a severe reduction in the number of growing follicles from the primary follicle stage onwards was observed. In the model of Hayes et al, daily AMH treatment seemed to affect FSH sensitivity more strongly than primordial follicle recruitment.…”
Section: Amh and Its Role In Ovarian Function In Pcosmentioning
confidence: 99%